The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3762/bjoc.13.4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of anti-oxidant and cytotoxic activities of novel 10-undecenoic acid methyl ester based lipoconjugates of phenolic acids

Abstract: The synthesis of five novel methyl 10-undecenoate-based lipoconjugates of phenolic acids from undecenoic acid was carried out. Undecenoic acid was methylated to methyl 10-undecenoate which was subjected to a thiol–ene reaction with cysteamine hydrochloride. Further amidation of the amine was carried out with different phenolic acids such as caffeic, ferulic, sinapic, coumaric and cinnamic acid. All synthesized compounds were fully characterized and their structures were confirmed by spectral data. The anti-oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 25 publications
(27 reference statements)
1
5
0
Order By: Relevance
“…In this regarding, presence of ether and pyrazole compounds in A. flavus extract play major roles as antioxidant and antimicrobial activities; this concurs with that reported in the previous studies (Jelena & Maja, 2015;Srivastava et al, 2015;Narra et al, 2017;Yadav et al, 2018). (Narra et al (2017) Moreover, the present investigation confirmed the presence of other bioactive compounds as Spirosten, Naphthalene, Trinolabdan and hexadecene that characterized by their antiproliferative activity, similarly with that reported previously (Huang et al, 2003;Sisa et al, 2003;Popova et al, 2009;Lu et al, 2015;Lemoreaux, 2017;Zheng et al, 2018).…”
Section: Candida Albicanssupporting
confidence: 93%
“…In this regarding, presence of ether and pyrazole compounds in A. flavus extract play major roles as antioxidant and antimicrobial activities; this concurs with that reported in the previous studies (Jelena & Maja, 2015;Srivastava et al, 2015;Narra et al, 2017;Yadav et al, 2018). (Narra et al (2017) Moreover, the present investigation confirmed the presence of other bioactive compounds as Spirosten, Naphthalene, Trinolabdan and hexadecene that characterized by their antiproliferative activity, similarly with that reported previously (Huang et al, 2003;Sisa et al, 2003;Popova et al, 2009;Lu et al, 2015;Lemoreaux, 2017;Zheng et al, 2018).…”
Section: Candida Albicanssupporting
confidence: 93%
“…Furthermore, undecanoic acid methyl ester, another important metabolite released by T . pinophilus SPJ22 has been found to possess antioxidant and antimicrobial properties [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The compound also showed antidiabetic effect by enhancing glucose uptake via activation of Akt and Erk1/2 in C2C12 myotubes. Undecanoic methyl esters are reported to have cytotoxic effect against breast, ovarian, prostrate and liver cancer cell lines with IC 50 values in the range of 10–140 μM [30].…”
Section: Discussionmentioning
confidence: 99%